A portable visual coffee ring based on carbon dot sensitized lanthanide complex coordination to detect bisphenol A in water. Issue 12 (4th March 2022) - Li, Yixiao; Min, Qi; Wang, Yunfei; Zhuang, Xuming; Hao, Xiaowen; Tian, Chunyuan; Fu, Xiuli; Luan, Feng
Abstract : A ratiometric portable visual fluorescence sensor of bisphenol A was developed based on carbon dot sensitized lanthanide complex coordination. Abstract : In this work, a ratiometric fluorescence sensor along with a portable coffee ring visualized detection method for bisphenol A (BPA) was developed based on carbon dots. The probe was formed by the coordination polymerization of Eu 3+ and 5′-adenosine monophosphate on the surface of carbon dots containing a large number of hydroxyl and carbonyl groups. The results showed that the fluorescence intensity ratio and the concentration of BPA had a good linear relationship in a wide range of 0.1–100 μM with a detection limit of 20 nM (S/N = 3). The recoveries of the added standard BPA in water samples ranged from 91.80 to 102.7% with relative standard deviation values no more than 1.84% ( n = 3). In addition, the changes of the fluorescence color of the CDs@Eu–AMP suspension with different BPA concentrations can be easily visualized under a UV lamp by the naked eye, which highlights the great potential of the coffee ring detection method for the fast and convenient monitoring of BPA in real water samples.